2013
DOI: 10.1177/0165025413486420
|View full text |Cite
|
Sign up to set email alerts
|

Adoptees’ curiosity and information-seeking about birth parents in emerging adulthood

Abstract: The Adoption Communication Pathway(ACP) model was used to test the potential mediating effect of curiosity on adoption information seeking in a sample of 143 emerging adult adoptees (mean age = 25.0 years) who were adopted as infants within the United States by parents of the same race. Adoptees were interviewed about their intentions and actions taken to gather new information about their birth mothers and fathers. As expected, level of curiosity was positively associated with information seeking behavior. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 24 publications
0
42
1
Order By: Relevance
“…Our interview data have also shown us that adolescents and young adults think about their adoptions very frequently, even though they do not necessarily initiate discussions about it with their parents. In fact, they often inhibit the desire to raise adoption issues with their adoptive parents or their birth parents, for fear of upsetting them (Garber, French, & Grotevant, 2015; Wrobel, Grotevant, Samek, & Von Korff, 2013). Data from this study and the earlier work of Dunbar make it clear that there are significant individual differences in adoption concern among adolescents; parents may have one child who is significantly preoccupied by adoption issues, whereas another may not be interested, at least at that point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Our interview data have also shown us that adolescents and young adults think about their adoptions very frequently, even though they do not necessarily initiate discussions about it with their parents. In fact, they often inhibit the desire to raise adoption issues with their adoptive parents or their birth parents, for fear of upsetting them (Garber, French, & Grotevant, 2015; Wrobel, Grotevant, Samek, & Von Korff, 2013). Data from this study and the earlier work of Dunbar make it clear that there are significant individual differences in adoption concern among adolescents; parents may have one child who is significantly preoccupied by adoption issues, whereas another may not be interested, at least at that point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents often vary in the extent to which they are interested in their own adoption such that some exhibit high levels of curiosity while others show little interest (Brodzinsky, ). In fact, Wrobel, Grotevant, Samek, and Von Korff () discovered that both male and female adoptees were moderately curious about their adoptions, and adoptee's level of curiosity was positively associated with information‐seeking behaviors. This study further revealed the complex process by which adoptees must negotiate internal barriers (e.g., not feeling ready, not wanting to hurt someone, perceived negative response from birth parent), interior facilitators (e.g., perceived positive response from birth parent, positive perceptions of adoption agency, being personally ready), external barriers (e.g., agency policies or fees, lack of time), and external facilitators (e.g., having resources such as money and information, receiving offers of assistance from adoptive parents or others) when seeking out new information (Wrobel et al, ).…”
Section: Applying and Adapting The Fac Model To The Foster Family Conmentioning
confidence: 99%
“…In fact, Wrobel, Grotevant, Samek, and Von Korff () discovered that both male and female adoptees were moderately curious about their adoptions, and adoptee's level of curiosity was positively associated with information‐seeking behaviors. This study further revealed the complex process by which adoptees must negotiate internal barriers (e.g., not feeling ready, not wanting to hurt someone, perceived negative response from birth parent), interior facilitators (e.g., perceived positive response from birth parent, positive perceptions of adoption agency, being personally ready), external barriers (e.g., agency policies or fees, lack of time), and external facilitators (e.g., having resources such as money and information, receiving offers of assistance from adoptive parents or others) when seeking out new information (Wrobel et al, ). The culmination of these studies indicates that adoptee information seeking is a dynamic process that takes place over several life stages, and open communication about adoption in the adoptive family tends to support adoptee information‐seeking behaviors (see Farr et al, ; Skinner‐Drawz, Wrobel, Grotevant, & Von Korff, ).…”
Section: Applying and Adapting The Fac Model To The Foster Family Conmentioning
confidence: 99%
“…Level of curiosity was also found to be positively associated with informationseeking behaviour regarding birth parents in adult adoptees (Wrobel et al, 2013). In particular, the reason for being adopted and medical histories of biological relatives are of a great concern.…”
mentioning
confidence: 90%
“…not feeling ready) increased curiosity but decreased informationseeking when adoptees searched for their birth mother whereas external barriers (e.g. agency policies) increased curiosity which in-turn increased information-seeking for birth fathers (Wrobel et al, 2013).…”
mentioning
confidence: 99%